Unlocking the power of investment decision making with MATLAB: A cutting-edge method for optimizing capacities - Perez-Campdesuner, Reyner; Sanchez-Rodriguez, Alexander; Garcia-Vidal, Gelmar; Martinez-Vivar, Rodobaldo (Nurture, 2023)
Purpose: The aim of this research was to present a method that would allow responding to both interests in a staggered and proportional way, in correspondence with existing financial availability. Design/Methodology/Approach: This research shows the results of the application of a methodological proposal programmed in MATLAB, which provided a solution to the described problem. Findings: The application was carried out in a small company, which has three fundamental products, and allowed to optimize the use of the available capital, increasing both the installed capacities and the potential demand for the products offered. Conclusion: It is possible to define an investment strategy that, based on the existence of an amount of financial availability, alternates the investment in the limiting capacity or the commercialization actions in correspondence with what is the limitation of the organization, which can be a limitation of capacity or market. This favors a systematic increase in the utility of the organization. Practical Implications: An analysis algorithm is developed that can serve as a guide for businessmen to design investment strategies aimed at increasing demand or capacity restrictions, as the case may be, based on financial availability and contributing to the systematic increase in the utility of the organization under study. Contribution to Literature: A method is presented that combines the analysis of capacity restrictions with those of demand restrictions, an aspect that is generally addressed in the literature independently.